2014
DOI: 10.5326/jaaha-ms-6130
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Ultrasonographic Findings of Uterine Neoplasms in Nine Dogs

Abstract: The records of nine female intact dogs with histologically confirmed uterine tumors were reviewed retrospectively, and the related radiographic and ultrasonographic signs of the lesions detected were recorded. Radiography revealed a soft-tissue opacity between the urinary bladder and colon in six of seven dogs with uterine body and/or cervical tumors, and a soft-tissue opacity in the midventral abdomen in two dogs with uterine horn tumors. Ultrasonography revealed masses in all dogs with uterine body/cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…Canine uterine neoplasias most commonly develop as focal soft tissue masses with variable sonographic characteristics . Dystrophic mineralization and/or osseous metaplasia have been identified radiographically and sonographically in some canine uterine tumors . In the present report, multifocal areas of mineralization were observed along the entire mucosal surface of the uterus via abdominal ultrasound.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Canine uterine neoplasias most commonly develop as focal soft tissue masses with variable sonographic characteristics . Dystrophic mineralization and/or osseous metaplasia have been identified radiographically and sonographically in some canine uterine tumors . In the present report, multifocal areas of mineralization were observed along the entire mucosal surface of the uterus via abdominal ultrasound.…”
Section: Discussionsupporting
confidence: 47%
“…Canine uterine neoplasias most commonly develop as focal soft tissue masses with variable sonographic characteristics . Dystrophic mineralization and/or osseous metaplasia have been identified radiographically and sonographically in some canine uterine tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Other mesenchymal and epithelial tumours are less frequently seen (Taylor, 2010). Very few reports of canine uterine carcinoma exist in the literature mainly affecting middle-aged or geriatric bitches (Vos 1988;Pena et al, 2006;Patsikas et al, 2014); however, it has been seen in a 2-yearold bitch treated with combined sex hormones, but the cause-and-effect association was not confirmed (Payne-Johnson et al, 1986) and in a 10-month-old entire golden retriever (Cave et al, 2002). Recently, the immunohistochemical characteristics of a canine endometrial adenocarcinoma were studied (Pires et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because proliferative changes in uterus and ovaries could be a consequence of continuing exposure to steroid hormones, the uterine epithelium may be prone to develop neoplasia at early life [ 20 ], as was observed in the present study. In a recent report by Patsikas et al [ 31 ], ultrasound examination of 9 dogs revealed the presence of masses with solid images, which were observed to be three cases of leiomyoma, two cases of adenocarcinomas, and one case of leiomyoma. In that same report, dogs exhibiting cysts and cystic masses at ultrasound evaluation of the uterus, those cysts and masses were identified as fibroleiomyoma and leiomyoma at microscopic evaluation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%